Uroscopy diagrams, judgment, and the perception of color in late medieval England. Issue 4 (2nd October 2022) - Boxer, Carly B.
Abstract: Late medieval English uroscopy diagrams depict twenty colors of urine in bright, often garish, colors and gold leaf, arranged in correspondence to digestive states. This article argues that the use of color in these diagrams reveals medieval ideas about the perception of color more broadly, and that the images themselves could train practices of comparative looking and visual judgment. Appearing in multiple formats, these images facilitated the theorization and practice of uroscopy—the diagnosis of an ailment by the appearance of a patient's urine—and survive in large numbers from late medieval England. Diagrams accompany treatises that describe at length the humoral causes, physical symptoms, and particular appearances of different colors of urine. Medieval digestive theory held that changes in the relative proportion of heat, cold, moisture, and dryness in the blood caused qualitative changes in the look of substances such as urine. Accounts of the appearance of bodily evidence in uroscopy treatises, however, relied on a slippery network of color descriptions and comparisons of colors of urine with other colorful objects. Diagrams made these relationships not only legible but also instructive. In juxtaposing text and image, this article incorporates uroscopy—perhaps the best documented medieval practical application of ideas about color—into broader discussions of medieval color theory.